Opportunistic predation of the Roadside Hawk (Rupornis magnirostris) on alates subterranean termites (Coptotermes testaceus) in southwestern Brazilian Amazon - Barbosa, Raul Afonso Pommer (2022)
We report the opportunistic predation of Roadside Hawk (Rupornis magnirostris - Accipitridae) on subterranean termite (Coptotermes testaceus - Rhinotermitidae). This predatory behaviour was observed during an avifauna survey in the municipality of Candeias do Jamari, Rondônia, Brazil, in the southwestern Brazilian Amazon. There was a great abundance of C. testaceus alates because of heavy rainfall. This is the season when C. testaceus colonies produce alates in large numbers to found new colonies. The Roadside Hawk stayed on its perch and captured winged termites with little energy expenditure. The bird in question appeared to take advantage of the termite mating flight to feed opportunistically on the abundant alates. Although feeding on insects by R. magnirostris is well known, this is the first documentation of feeding on termite alates.